2009
DOI: 10.4028/www.scientific.net/msf.615-617.251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Screw Dislocations in a 4H-Silicon Carbide Diode Using X-Ray Microbeam Three-Dimensional Topography

Abstract: Abstract. This paper describes the study of non-hollow-core elementary screw dislocations (SDs) in silicon carbide (SiC) diodes using X-ray microbeam three-dimensional topography. Strain analysis shows that typical screw dislocations having a symmetric strain field tend to cause microplasma breakdown, whereas deformed SDs do not. The symmetry break in SDs will relax the focussing of strain and lessen the formation of defects, thereby leading to the desirable non-leak property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…[3][4][5] Principally, TSD in 4H-SiC has the 〈0001〉 (c-) component of the Burgers vector b, and the propagation direction of TSD is parallel to b. Photoluminescence (PL) measurement, transmission electron microscopy and X-ray topography have been used to investigate the TSD structure in SiC. Tanuma et al 6) showed the existence of symmetry and asymmetry in the strain field of local TSD using X-ray topography with a micro beam. Nagano et al 7,8) demonstrated the existence of TSDs inclined from the 〈0001〉 axis by a cross-sectional PL observation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Principally, TSD in 4H-SiC has the 〈0001〉 (c-) component of the Burgers vector b, and the propagation direction of TSD is parallel to b. Photoluminescence (PL) measurement, transmission electron microscopy and X-ray topography have been used to investigate the TSD structure in SiC. Tanuma et al 6) showed the existence of symmetry and asymmetry in the strain field of local TSD using X-ray topography with a micro beam. Nagano et al 7,8) demonstrated the existence of TSDs inclined from the 〈0001〉 axis by a cross-sectional PL observation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, very high voltage SiC power devices with a thick epilayer require defect imaging as deep as 100-200 µm. X-ray microbeam 3D topography has been successfully applied for the imaging of TSDs, 14) BPDs, and TEDs, 15,16) although this technique requires a large-scale synchrotron radiation facility.…”
mentioning
confidence: 99%
“…X-ray 3D topography has been successfully applied to imaging TSDs, 5) BPDs, and TEDs. 6,7) However, this technique requires a large-scale synchrotron-radiation facility.…”
mentioning
confidence: 99%